Association between patellar tendon moment arm and running performance in endurance runners - Tamura, Y.; Jee, E.; Kouzaki, K.; Kotani, T.; Nakazato, K. (Physiological Reports, 2021)
A shorter joint moment arm (MA) may help maintain the necessary muscle force when muscle contractions are repeated. This beneficial effect may contribute to reducing the energy cost during running. In this study, we examined the correlation between patellar tendon MA and running performance in endurance runners. The patellar tendon MA and quadriceps femoris muscle volume (MV) in 42 male endurance runners and 14 body size-matched male untrained participants were measured using a 1.5-T magnetic resonance system. The patellar tendon MA was significantly shorter in endurance runners than in untrained participants (p = 0.034, d = 0.65). In endurance runners, shorter patellar tendon MA correlated significantly with better personal best 5000-m race rime (r = 0.322, p = 0.034). A trend toward such a significant correlation was obtained between quadriceps femoris MV and personal best 5000-m race time (r = 0.303, p = 0.051). Although the correlation between patellar tendon MA and personal best 5000-m race time did not remain significant after adjusting for the quadriceps femoris MV (partial r = 0.247, p = 0.120), a stepwise multiple regression analysis (conducted with body height, body mass, patellar tendon MA, and quadriceps femoris MV) selected the patellar tendon MA (ß = 0.322) as only a predictive variable for the personal best 5000-m race time (adjusted R2 = 0.081, p = 0.038). These findings suggest that the shorter patellar tendon MA, partially accorded with the smaller quadriceps femoris size, may be a favorable morphological variable for better running performance in endurance runners.